Peningkatan Mutu Madrasah melalui Modal Sosial - Ju’subaidi, Ju’subaidi (Nadwa, 2012)
This paper attempts to examine the important role of social capital in the meninges-forces madrasah education quality. Madrasah as national education subsystem has a heavy burden in carrying out the mandate of the law. The biggest problem is the activity of improving the quality of education that is determined by the achievement of the ultimate goal of education effectively and more efficiently. That goal is the realization of academic ability, moral and social. Structure and values of the communities around it is actually a social capital that should be used by the madrassa to improve the quality of education. Social capital is a means of achieving national education goals. AbstrakTulisan ini mencoba mengkaji peran penting modal sosial dalam peningkatan mutu pendidikan madrasah. Madrasah sebagai subsistem pendidikan nasional memiliki beban yang berat dalam mengemban amanat undang-undang. Problem terbesar adalah kegiatan meningkatkan mutu pendidikan yang ditentukan oleh ketercapaian tujuan akhir pendidikan secara efektif dan lebih efisien. Tujuan itu adalah terwujudnya kemampuan akademik, moral dan sosial. Struktur dan nilainilai yang dimiliki masyarakat sekitar sebenarnya merupakan modal sosial yang seharusnya dimanfaatkan oleh madrasah untuk meningkatkan mutu pendidikannya. Modal sosial ini menjadi sarana mencapai tujuan pendidikan nasional.